Brain Radiation Information Data Exchange (BRIDE): integration of experimental data from low-dose ionising radiation research for pathway discovery. Issue 1 (December 2016) - Karapiperis, Christos; Kempf, Stefan; Quintens, Roel; Azimzadeh, Omid; Vidal, Victoria; Pazzaglia, Simonetta; Bazyka, Dimitry; Mastroberardino, Pier; Scouras, Zacharias; Tapio, Soile; Benotmane, Mohammed; Ouzounis, Christos
Abstract Background The underlying molecular processes representing stress responses to low-dose ionising radiation (LDIR) in mammals are just beginning to be understood. In particular, LDIR effects on the brain and their possible association with neurodegenerative disease are currently being explored using omics technologies. Results We describe a light-weight approach for the storage, analysis and distribution of relevant LDIR omics datasets. The data integration platform, called BRIDE, contains information from the literature as well as experimental information from transcriptomics and proteomics studies. It deploys a hybrid, distributed solution using both local storage and cloud technology. Conclusions BRIDE can act as a knowledge broker for LDIR researchers, to facilitate molecular research on the systems biology of LDIR response in mammals. Its flexible design can capture a range of experimental information for genomics, epigenomics, transcriptomics, and proteomics. The data collection is available at: <bride.azurewebsites.net>.